Respostas

2014-02-22T10:43:55-03:00
Reposta

x² - 8x + 7 = 0

Δ  = b² - 4ac
Δ = -8² - 4.1.7
Δ = 64 - 28
Δ =  36

x = -b +- √Δ  /2a

x = -(-8) +- √36 /2.1

x = 8 +- 6 /2

x' = 8 + 6 /2
x' = 14/2
x' = 7

x'' = 8 - 6/2
x'' = 2/2
x'' = 1

S = (7 , 1)
2014-02-22T10:45:38-03:00
X² - 8x + 7 = 0 ~> a = 1 , b = -8 , c = 7

Δ = b² - 4ac
Δ = (-8)² - 4.1.7
Δ = 64 - 28
Δ = 36

x = -b ± √Δ
         2a

x = -(-8) ± √36
          2.1

x =± 6 
        2

x' = 8 + 6  = 14 = 7               x" = 8 - 6 = 2 = 1
         2         2                               2      2

S = { 1 , 7 }
1 5 1